DEMOKRASI DALAM TEOSOFI IBN RUSYD TERHADAP TEORI PLATO - Nur Sakina Harahap; Nur Ikhlas (RUSYDIAH: Jurnal Pemikiran Islam, 2022)
Abstract This study discusses the concept of principles regarding Ibn Rushd's politics he calls his thoughts with the term "al-Jumhuriyyah wa al-ahkaam"which means Republic and law. Political thought is an integration of 'science and' charity. In this context, Ibn Rushd put forward more independence and freedom. However, according to him, independence and freedom are not without regulatory actions, but independence and freedom according to religious principles. in the perspective of Ibn Rushd, is a mirror of democracy (as-siyasah al-jamiah). Like the thoughts of the previous philosophers who reconciled between religion and philosophy. According to Ibn Rushd, reason and religion are not something that need to be contradicted and therefore, it is important for reason and religion to work together to uphold the principles of democracy (as-siyasah al-jamiah) in a country. The establishment of a free mind (as-siyasah al-jamiah) is a distinctive feature of Ibn Rushd's political democracy. The upholding of the minds of the largest group is called the majority (the majority), the establishment of the minds of the small groups is called the minority, and the establishment of free thoughts from everyone is the essence of democracy (as-siyasah al-jamiah). Therefore, the democratic state (as-siyasah al-jamiah) desired by Ibn Rushd is a state of ratio and religion, a state of knowledge and belief, a worldly and spiritual state.